Mutations That Affect the Tropism of DA and GDVII Strains of Theiler's Virus In Vitro Influence Sialic Acid Binding and Pathogenicity - Jnaoui, Karima (American Society for Microbiology, 2002)
Theiler's murine encephalomyelitis virus (TMEV) is a natural pathogen of the mouse. The different strains of TMEV are divided into two subgroups according to the pathology they provoke. The neurovirulent strains GDVII and FA induce an acute fatal encephalitis, while persistent strains, like DA and BeAn, cause a chronic demyelinating disease associated with viral persistence in the central nervous system. Different receptor usage was proposed to account for most of the phenotype difference between neurovirulent and persistent strains. Persistent but not neurovirulent strains were shown to bind sialic acid. We characterized DA and GDVII derivatives adapted to grow on CHO-K1 cells. Expression of glycosaminoglycans did not influence infection of CHO-K1 cells by parental and adapted viruses. Mutations resulting from adaptation of DA and GDVII to CHO-K1 cells notably mapped to the well-characterized VP1 CD and VP2 EF loops of the capsid. Adaptation of the DA virus to CHO-K1 cells correlated with decreased sialic acid usage for entry. In contrast, adaptation of the GDVII virus to CHO-K1 cells correlated with the appearance of a weak sialic acid usage for entry. The sialic acid binding capacity of the GDVII variant resulted from a single amino acid mutation (VP1-51, Asn→Ser) located out of the sialic acid binding region defined for virus DA. Mutations affecting tropism in vitro and sialic acid binding dramatically affected the persistence and neurovirulence of the viruses.